Sistem Informasi Pengembangan Website Digitalisasi Katalog Lontar Di Kabupaten Tabanan Kecamatan Selemadeg - Sudarsana, I Made; Suradarma, Ida Bagus; Meitridwiastiti, Anak Agung Ayu (Jayapangus Press, 2025)
Strengthening the preservation of lontar in the form of digitisation needs to continue to be developed as an effort to maintain and develop the knowledge stored in lontar so that it is suitable for reading and use in everyday life. The purpose of this study is as a form of preservation, to create a catalog of lontar in tabanan regency, selemadeg district through the process of developing a digitalization website for the lontar catalog in tabanan regency. The method used in this research on the digitisation of lontar catalogues with web-based information systems uses a waterfall approach, which consists of concept planning, modelling (design), implementation, testing and maintenance stages. The results of this study found that lontars that were 30 years old, there were lontars that had not been properly stored and were left alone by their owners, so that the lontars were damaged by termites and rodents, therefore there must be an effort to save the storage of lontar owners so that lontars do not become extinct. Where researchers have carried out the process of digitizing lontar manuscripts in tabanan regency, selemadeg district so that the original physical form of the lontar manuscript as an ancestral heritage can be preserved and the information contained therein can be saved. All lontar manuscripts in tabanan regency, selemadeg district are cataloged so that they are easy to store and access. Lontar that has been made into digital form currently contains 31 digital lontar manuscripts that will be cataloged to facilitate providing information online, in the form of digital storage which makes it easier to identify the owner of the original lontar containing the status and origin of the lontar. This research aims to save lontar by creating a catalog of lontar in tabanan regency as a form of preserving local culture for lontar owners and future generations.